In Situ Evidence for Quantitative Nitrogen Fixation in a Temperate Perennial Grass Ecosystem - Sarah S. Roley; Carmella Vizza; Kevin Kahmark; Sean J. L. Murphy; Daniel H. Buckley; G. Philip Robertson (Ecosystems, 2026)
Biological nitrogen (N) fixation is an important terrestrial ecosystem N input that occurs in both symbiotic and non-symbiotic associations with plants. Non-symbiotic nitrogen fixation (NSNF) has been documented in many places, including soils, but the magnitude of its inputs, along with drivers of NSNF rates, remains uncertain due to methodological challenges. We measured NSNF by applying a 15 N 2 tracer to field mesocosms that contained a reassembled soil profile (75 cm deep) with mature switchgrass ( Panicum virgatum ) at a site in southwest Michigan, USA. We measured NSNF both early and mid-growing season. We found fixed N throughout the entire soil profile, but fixed N declined with depth as did the soil C:N ratio. During the early growing season, most recently fixed N accumulated in the roots, but in the later incubation, fixed N accumulated equally in roots and in aboveground tissues. Annually scaled NSNF rates agreed with those from mass balance within an order of magnitude. Based on our mesocosm measurements and mass balance calculations, we estimate that NSNF inputs to switchgrass at our study site were 2–12 kg N ha −1 yr −1 , which represented 27–68% of annual plant N needs.